Genetic variants in pachyonychia congenita-associated keratins increase susceptibility to tooth decay. - Olivier Duverger; Jenna C Carlson; Chelsea M Karacz; Mary E Schwartz; Michael A Cross; Mary L Marazita; John R Shaffer; Maria I Morasso (PLoS Genetics)
Pachyonychia congenita (PC) is a cutaneous disorder primarily characterized by nail dystrophy and painful palmoplantar keratoderma. PC is caused by mutations in KRT6A, KRT6B, KRT6C, KRT16, and KRT17, a set of keratin genes expressed in the nail bed, palmoplantar epidermis, oral mucosal epithelium, hair follicle and sweat gland. RNA-seq analysis revealed that all PC-associated keratins (except for Krt6c that does exist in the mouse genome) are expressed in the mouse enamel organ. We further demonstrated that these keratins are produced by ameloblasts and are incorporated into mature human enamel. Using genetic and intraoral examination data from 573 adults and 449 children, we identified several missense polymorphisms in KRT6A, KRT6B and KRT6C that lead to a higher risk for dental caries. Structural analysis of teeth from a PC patient carrying a p.Asn171Lys substitution in keratin-6a (K6a) revealed disruption of enamel rod sheaths resulting in altered rod shape and distribution. Finally, this PC-associated substitution as well as more frequent caries-associated SNPs, found in two of the KRT6 genes, that result in p.Ser143Asn substitution (rs28538343 in KRT6B and rs151117600 in KRT6C), alter the assembly of K6 filaments in ameloblast-like cells. These results identify a new set of keratins involved in tooth enamel formation, distinguish novel susceptibility loci for tooth decay and reveal additional clinical features of pachyonychia congenita.